Efficacy of Ayurveda Against Oral Submucous Fibrosis - A Case Study - Sharma, Aparna; Kumar, Ashok; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2022)
Oral Submucous Fibrosis is on a steady rise due to excessive use of betel nut chewing and tobacco consumption in various forms. Despite habit corrections, the fibrosis stays refractory and grossly hanoers the quality of life. Young Males being the most affected group, this condition has more reflects adversities beyond one’s individual health. Ayurveda interventions show significant improvements in many symptoms. Gandush is such a local Panchakarma therapy. An elderly female, known case of OSMF was taken up at the NIA deemed to be University Hospital, Jaipur, assessed on a specially designed Case Record Proforma and administered Gandush therapy for 2 month & significant reduction in most symptoms recorded.